Determinasi Manajemen Laba: Kajian Empiris Pada Perusahaan Real Estate Periode 2020-2024 - Jessie Jessie; Thomas Averio (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to examine the influence of political connections, gender diversity, financial distress, and operating cash flow on earnings management in the real estate sector. The population consists of companies listed on the Indonesia Stock Exchange from 2020 to 2024. Samples were obtained through purposive sampling, involving 39 companies over 5 years, resulting in 195 total observations. The study employs quantitative methods with panel data regression analysis, using SPSS 26 software. The results indicate that financial distress and operating cash flow have a positive influence on earnings management, while political connections and gender diversity have a negative influence. In this studs, the coefficient of determination is 52.5%.The main contribution of this study is to provide a foundation for real estate company management to strengthen internal oversight to reduce earnings management during high financial distress, through independent audits or funding diversification. Investors and creditors can utilize these findings as risk indicators, where companies with low political connections, high gender diversity, or high operating cash flow are more transparent, thereby reducing investment risk in sectors vulnerable to economic fluctuations.